Focus on Asia Politics.
Summary: "Asia Pacific encompasses a broad range of political systems. This is evident first of all in relation to the major powers. Both the United States and Japan have liberal democratic political systems. China on the other hand has an authoritarian political system under the leadership of the Chinese Communist Party. A number of the states in both Northeast and Southeast Asia are based on democratic principles; many have experienced democratization in recent times. In Northeast Asia, South Korea and Taiwan have undergone democratization since the late 1980s. Apart from China, there are communist-oriented authoritarian governments in North Korea, Vietnam, and Laos. While there have been moves toward reform in Vietnam, North Korea remains as the world’s sole remnant of Stalinism. Burma is the main instance of a military-dominated regime in the region, and Brunei is ruled by a sultanate. The relationship between globalization, sovereignty and security is now more inextricably linked in the normally competing scholarly literatures of security studies and international political economy compared to any time in the recent past. Trends in contemporary world order can only be understood by examining the changing relationship between sovereignty and security under conditions of economic globalization. Tensions have continued throughout the early twenty-first century in relation to both Taiwan and Korea. Are these tensions likely to result in war at some point? In Southeast Asia the various states have faced numerous “nation building” challenges, none more so than Indonesia. Many groups oppose the authority of the existing states, and these tensions often spill over into the international arena. Throughout Asia Pacific one can also observe the expanding presence of regional and global organizations. Does this presence amount to much, and if so what? Are we moving into an era when states, both major and lesser powers, will become less significant for Asia Pacific international politics? This book is concerned with this whole range of issues and questions as they appear in the current phase of world politics in Asia Pacific. This book provides a comprehensive,but accessible, introduction to political change and processes in Southeast Asia. This book explores political participation in Asia and how democracy and authoritarianism function under economic relations. This is an introduction to ecological footprint analysis, showing how it can be done, and how to measure the footprints of activities, lifestyles, organizations and regions."--Back cover